Banking risks: enhancing requirements concerning risk management and information disclosure - Kryvych, Ya. M.; Makarenko, I. O. (Видавництво Львівської політехніки, 2014)
The article deals with the nature, basic principles and objectives of the bank risk management system under modern conditions and the requirements of regulators as to the transparency of their activities. The authors have developed a scheme of the bank risk management and justified basic directions of disclosing information about banks on the basis of international approaches in the context of introduction of the International Financial Reporting Standards. Розглянуто сутність, основні принципи та завдання реалізації системи ризик-менеджменту банку в сучасних умовах, а також вимоги регуляторів щодо забезпечення прозорості його діяльності. Автори розробили схему управління ризиками банку та обґрунтували основні напрями розкриття інформації про них на основі міжнародних підходів у контексті переходу банків на міжнародні стандарти фінансової звітності.
Ризики банків: посилення вимог щодо управління та розкриття інформації
Keywords: risk; risk management; information disclosure; transparency and corporate governance; ризик; управління ризиками; розкриття інформації; прозорість; корпоративне управління